Increasing Student Interest and Engagement with Business Cases by Turning Them into Consulting Exercises1. (3rd October 2013) - Erzurumlu, S. Sinan; Rollag, Keith
ABSTRACT: How can you get undergraduate students more interested and engaged with business cases? Instead of using the traditional case teaching format, turn the case into a consulting exercise. Give students only the managerial dilemma and some starting information, form them into consulting teams, and then have each team requests additional case information by submitting a restricted number of questions. Through successive rounds, teams will gather enough information and data to analyze the situation and develop a set of recommendations. This approach transforms case‐based learning from a passive analysis of case details to an active process of discovery through smart questioning.